2016
DOI: 10.1038/nrneph.2016.54
|View full text |Cite
|
Sign up to set email alerts
|

Developmental signalling pathways in renal fibrosis: the roles of Notch, Wnt and Hedgehog

Abstract: Kidney fibrosis is the histological manifestation of functional decline in the kidney. Fibrosis is a reactive process that develops in response to excessive epithelial injury and inflammation. Here, we describe how three key developmental signalling pathways—Notch, Wnt and Hedgehog—are reactivated in response to kidney injury. Although transient activation of these pathways is needed for repair of injured tissue, their sustained activation promotes fibrosis. Excessive Wnt and Notch expression prohibit epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
241
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(266 citation statements)
references
References 150 publications
4
241
0
1
Order By: Relevance
“…Accordingly, we generated mice with podocyte-specific knockout of EZH2. To do this, we mated podocin-Cre + mice that express Cre recombinase in podocytes under the control of the human podocin NPHS2 promoter (19) with Ezh2 fl/fl mice that were generated by the introduction of LoxP sites into the Ezh2 locus flanking exons [16][17][18][19], which encode the essential SET domain of the protein (20 Figure 1B) and by immunoblotting primary cultured podocytes ( Figure 1C) and was accompanied by an approximately 50% reduction in podocyte H3K27me3 content ( Figure 1D). Despite this Ctrl (n = 3) and EZH2 podKO (n = 3) mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we generated mice with podocyte-specific knockout of EZH2. To do this, we mated podocin-Cre + mice that express Cre recombinase in podocytes under the control of the human podocin NPHS2 promoter (19) with Ezh2 fl/fl mice that were generated by the introduction of LoxP sites into the Ezh2 locus flanking exons [16][17][18][19], which encode the essential SET domain of the protein (20 Figure 1B) and by immunoblotting primary cultured podocytes ( Figure 1C) and was accompanied by an approximately 50% reduction in podocyte H3K27me3 content ( Figure 1D). Despite this Ctrl (n = 3) and EZH2 podKO (n = 3) mice.…”
Section: Resultsmentioning
confidence: 99%
“…Before doing this, we administered EPZ-6438 to adriamycin-sensitive BALB/c mice and observed an increase in albuminuria with the EZH2 inhibitor following adriamycin injection (Supplemental Figure 5), which paralleled the increase in albuminuria we had seen in adriamycin-treated EZH2 podKO mice ( Figure 1F). In cultured mouse podocytes, EZH2 inhibition with EPZ-6438 led to a decrease in H3K27me3 levels glomerular disease is also associated with the reactivation of developmental pathways (18). However, unlike cancer cells, podocytes are postmitotic.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies have identified loci associated with increased susceptibility to renal dysfunction in humans (12,13). Additionally, mouse models and genome-wide transcriptome analyses of kidneys from patients with CKD and fibrosis have facilitated the identification of a number of signaling pathways associated with renal fibrosis, including the Notch, Wnt, and Hedgehog pathways (3). The further identification of signaling pathways associated with fibrosis increases the potential opportunities for targeted therapy to thwart fibrosis.…”
mentioning
confidence: 99%
“…Upregulated Wnt proteins may trigger pod ocyte injury or interstitial fibrosis in mice with Adria­mycin nephropathy or UUO nephropathy [30, 31]. In addition to animal models, the relationship of Wnt/β-catenin signaling activation with CKD has also been reported in patients with IgA nephropathy, HIV-induced nephropathy, diabetic kidney disease, and focal segmental glomerulosclerosis [32, 33]. A microarray analysis study revealed that the expression profile of a subset of 21 Wnt-related genes may differentiate patients with IgA nephropathy from healthy controls.…”
Section: Discussionmentioning
confidence: 99%